Petrology of Exposed Basement Rocks around Shintaku of North Central Nigeria - Odedede, O. (Journal of Scientific Research, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> The study area is part of the Basement Complex of North Central Nigeria. The study aims at identifying the rock types and interpretation of the structural elements. The major rock units in the area comprises of porphyritic granite, gneiss and schist. Structural evidence shows that the rocks are deformed and where intruded by the granite. Petrographic analysis reveals the existence of feldspar phenocrysts in a groundmass of quartz and biotite. The granite is composed of quartz (25-35%), plagioclase (15-20%), orthoclase (10-20%), microcline (5-25%), biotite (15-20%) and other accessory minerals. The granites displayed a porphyritic texture while the schist and gneisses exhibit planar and linear structures. Variation in structural trend and mineralogical composition is due to the series of deformational activities which has affected the rocks during geologic time. Keywords: Monzogranite; Porphyritic; Deformation; Fractionation. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i3.15233 J. Sci. Res. 5 (3), 489-497 (2013)